ANALYSIS OF LIQUIDITY, SOLVENCY, PROFITABILITY AT UD. RIFQI JAYA (Universitas Dr. Soetomo, 2022)
The purpose of this research conducted by the author is to analyze the financial statements of UD. Rifqi Jaya uses 3 methods namely liquidity analysis, solvency and profitability. The object of this research is the financial statements of UD. Rifqi Jaya from 2015 to 2017. In this study, the author used a qualitative descriptive approach. Based on the analysis liquidity ratio, the financial condition of UD. Rifqi Jaya can be said quite good because it will have no trouble paying their short-term debts. Meanwhile, the solvency analysis show thats total assets and capital are greater than total liabilities, so that the company is able pay their obligations. Likewise in the analysis of profitability, UD. Rifqi Jaya has the potential to increase net income, so that it can pay its obligations very well.